10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundHope is a key psychological and existential resource for patients with cancer and is associated with adaptation. From a holistic nursing perspective, identifying factors that foster hope may inform person-centered care. This study examined the associations of spiritual intelligence and self-compassion with hope among patients with cancer within a holistic nursing framework, with the aim of improving understanding of internal resources related to whole-person adaptation.MethodThis descriptive-analytical cross-sectional study was conducted in 2024 among 100 hospitalized patients with cancer in Kerman, Iran. Participants were selected using systematic random sampling. Data were collected using demographic, Hope, Spiritual Intelligence, and Self-Compassion questionnaires. Pearson correlation and hierarchical multiple regression analyses were performed.ResultsSpiritual intelligence was positively correlated with hope (r = 0.40, p < .001), whereas self-compassion was not significantly associated with hope (r = -0.04, p = .69). In the regression model, spiritual intelligence emerged as a significant predictor of hope, whereas self-compassion showed no independent association.ConclusionSpiritual intelligence showed a positive association with hope in patients with cancer, whereas self-compassion was not independently associated. These results underscore the importance of spiritual resources in patients' psychological adaptation and support the integration of spiritual care within holistic nursing practice.